THE TEST ACTIVITIES ANTIBACTERIALS SEAWEED EXTRACT (Eucheuma cottonii) AGAINST BACTERIA Staphylococcus aureus AND BACTERIA Escherichia coli - Sari, N. Ira; Sukmiwati, Mery; ', Megawati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Eucheuma cottonii seaweed is one of the plants that have bioactive compounds that can produce secondary metabolites that act as antibacterial, antioxidant, anticoagulant. This study aimed to find out that Eucheuma cottonii seaweed extracts have antibacterial compounds that can inhibit the bacteria Staphylococcus aureus and Escherichia coli bacteria as well as determine the minimum inhibitory zone diameters in bacteria Staphylococcus aureus and Escherichia coli. The method used is an experimental method that did extract manufacture seaweed (Eucheuma cottonii). The concentration of seaweed extract used was Er1 (0,02%),Er2 (0,1%),Er3 (0,5%). The experiments were performed with three replications.Results of research Eucheuma cottonii extract has antibacterial effects against bacteria Staphyloccocus aureus and Escherichia coli are indicated by the formation of inhibition zone around the well in order. The minimum inhibitory concentration Eucheuma cottonii extract against Staphylococcus aureus was 0,02% with an average inhibition zone of 10,00 ± 2,64mm and for the bacteria Escherichia coli 0,02% with an average inhibition zone of 0,67 ± 1,15mm.Keywords: Antibacterial activity, Eucheuma cottonii, Staphylococcus aureus, Escherichia coli